2015
DOI: 10.1021/jacs.5b04501
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic Lipopeptides Derived from Nisin Display Antibacterial Activity and Lipid II Binding on Par with That of the Parent Compound

Abstract: The lipid II-binding N-terminus of nisin, comprising the so-called A/B ring system, was synthetically modified to provide antibacterially active and proteolytically stable derivatives. A variety of lipids were coupled to the C-terminus of the nisin A/B ring system to generate semisynthetic constructs that display potent inhibition of bacterial growth, with activities approaching that of nisin itself. Most notable was the activity observed against clinically relevant bacterial strains including MRSA and VRE. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 45 publications
1
78
0
Order By: Relevance
“…Moreover, conjugate addition of water to Dha, and hydrolytic cleavage at this site are known degradation reactions . Despite the potential of Nisin as an antibiotic, to the best of our knowledge, no catalytic methods for modification have been reported, and stoichiometric chemical modifications are scarce …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, conjugate addition of water to Dha, and hydrolytic cleavage at this site are known degradation reactions . Despite the potential of Nisin as an antibiotic, to the best of our knowledge, no catalytic methods for modification have been reported, and stoichiometric chemical modifications are scarce …”
Section: Resultsmentioning
confidence: 99%
“…Selective chemical modification of RiPPs offers the possibility of further improving their properties and/or activity. A plethora of selective, bioorthogonal reactions for the modification of specific amino acid residues in proteins and peptides have been developed, some of which have been applied to RiPPs . However, methods for selective methionine modification are rare .…”
Section: Figurementioning
confidence: 99%
“…However, rings A–B are inactive on their own . It is suggested that upon pyrophosphate cage formation, the rings C–E (C‐terminus) of nisin insert into the lipid bilayer, thereby facilitating the assembly of nisin‐lipid II pore complex which leads to the lysis of bacteria . This dual mechanism‐of‐action makes nisin a very potent Gram‐positive antibacterial agent.…”
Section: Lipid II Inhibitors As Therapeutic Agentsmentioning
confidence: 99%
“…Semisynthetic analogues have been developed whereby the C–E domain of the natural product was replaced with various lipid substituents. Several of these derivatives that showed enhanced proteolytic stability and potent antibacterial activity hold great therapeutic promise …”
Section: Lipid II Inhibitors As Therapeutic Agentsmentioning
confidence: 99%